Psychology of high risk driving (review of foreign studies) - Bulygina V.G.; Dubinsky A.A.; Shport S.V.; Kalinkin D.S. (Психология и право, 2016)
The article presents a brief review of foreign theoretical concepts, empirical data and methodological approaches to the problem of high risk driving. There were defined and described the factors of dangerous driving: factors of external environment and internal factors, including age, fatigue, use of medications, alcohol and drugs, personal styles, impaired sensory analyzers, neurological and cognitive disorders, emotional states, styles of responding to stress. Emphasizes the role of reduction of cognitive functioning, acquired brain injury, persistent or progressive neurological diseases, and acquired somatic disorders. The outline of its main models of driving: motivational, models of information processing, hierarchical management model. A separate section of the article focuses on cognitive factors, describes a wide spectrum of disorders of cognitive functions that may potentially impair driving safety. The theoretical and methodological grounds and empirical studies of cognitive functioning are described. Discuss prospects and limitations in studies of cognitive functioning, the predictive value of some tests, including neuropsychological. The conclusion made about the need for standardization and validation the Protocol of assessment drivers and candidates for drivers, also the necessity of the introduction of a common approach for all medical workers and specialists of nonmedical profile, in order to overcome the existing differences in estimates in the implementation of medical examination, expert activity and enforcement.